2004
DOI: 10.1007/s10334-004-0042-z
|View full text |Cite
|
Sign up to set email alerts
|

Effect of new manganese contrast agent on tissue intensities in human volunteers: comparison of 0.23, 0.6 and 1.5 T MRI, a part of a phase I trial

Abstract: To evaluate the effect of a new oral manganese contrast agent (CMC-001) on magnetic resonance imaging (MRI) intensities at different magnetic field strengths. Twelve healthy volunteers underwent abdominal MRI 1 week before and within 2.5-4.5 h after CMC-001 (MnCl(2) and absorption promoters dissolved in water) intake at three different MR scanners of 0.23, 0.6 and 1.5 T. Image contrast and intensity enhancement of liver and pancreas were analysed relatively to muscle and fat intensities. Manganese blood levels… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
26
0

Year Published

2005
2005
2016
2016

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(26 citation statements)
references
References 13 publications
0
26
0
Order By: Relevance
“…The observed AE after the administration of 1.6 g of CMC-001 were related to the high ion-content resulting in gastrointestinal discomfort, diarrhoea and nausea. Although not serious, AE after CMC-001 were numerous and clearly of higher frequency than those reported by others, being a factor that could potentially inhibit a widespread use (83)(84)(85)(86). Therefore we initiated the investigation presented in study IV, with the aim to investigate whether lowering the dose of MnCl 2 tetrahydrate could result in fewer AE but with a sufficient diagnostic imaging quality.…”
Section: Studies III and Ivmentioning
confidence: 99%
“…The observed AE after the administration of 1.6 g of CMC-001 were related to the high ion-content resulting in gastrointestinal discomfort, diarrhoea and nausea. Although not serious, AE after CMC-001 were numerous and clearly of higher frequency than those reported by others, being a factor that could potentially inhibit a widespread use (83)(84)(85)(86). Therefore we initiated the investigation presented in study IV, with the aim to investigate whether lowering the dose of MnCl 2 tetrahydrate could result in fewer AE but with a sufficient diagnostic imaging quality.…”
Section: Studies III and Ivmentioning
confidence: 99%
“…In this way, manganese neurotoxicity is caused by mine dust inhalation or intravenous administration but rarely by oral intake [34,35]. The manganese metabolic pathway adapts to oral MRI contrast agents containing manganese, and the contrast effect of this oral contrast agent based on manganese is limited to liver and intestine [36,37].…”
Section: Manganesementioning
confidence: 99%
“…During the first passage of the liver, the organ takes up approximately 95% of the manganese [7][8][9][10], leaving only tiny amounts in the liver veins. Chabanova et al [4] were not able to measure increased levels of manganese in the peripheral blood for 25 h in healthy volunteers after the intake of CMC-001. This is also confirmed by a lack of pancreas and kidney enhancement-a feature seen after the administration of Fig.…”
Section: Discussionmentioning
confidence: 98%
“…For several years it has been possible to administer manganese for imaging of the liver and biliary tract intravenously [1,2]. Recently, it has been shown that it is also possible to administer manganese for liver and biliary imaging orally in healthy volunteers [3,4]. Oral administration offers several practical and physiological advantages [3], such as: it can be administered outside the MR room and even at home, it contains only nutritional ingredients, reducing the risk of adverse reactions, manganese enters mainly the enterohepatic circulation, the concentration is increased in the portal vein, but not in the hepatic artery, and the signal intensity of the bowel content is increased.…”
Section: Introductionmentioning
confidence: 99%